2010
DOI: 10.1071/fp09269
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of halophytes: multiple origins of salt tolerance in land plants

Abstract: Abstract. The evolution of salt tolerance is interesting for several reasons. First, since salt-tolerant plants (halophytes) employ several different mechanisms to deal with salt, the evolution of salt tolerance represents a fascinating case study in the evolution of a complex trait. Second, the diversity of mechanisms employed by halophytes, based on processes common to all plants, sheds light on the way that a plant's physiology can become adapted to deal with extreme conditions. Third, as the amount of salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
394
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 614 publications
(410 citation statements)
references
References 66 publications
6
394
0
10
Order By: Relevance
“…Briefly, they reported that studies of halophyte growth at high concentrations of salts 'offer a rather bewildering array of data'. As halophytes occur in at least 37 orders of plants, (see also Flowers et al 2010), this should not be unexpected. Optimal growth salinities range from 20 to 500 mM with large differences even within single genera (e.g.…”
Section: The Problem Of Organismal Integration In Saline Environmentsmentioning
confidence: 99%
“…Briefly, they reported that studies of halophyte growth at high concentrations of salts 'offer a rather bewildering array of data'. As halophytes occur in at least 37 orders of plants, (see also Flowers et al 2010), this should not be unexpected. Optimal growth salinities range from 20 to 500 mM with large differences even within single genera (e.g.…”
Section: The Problem Of Organismal Integration In Saline Environmentsmentioning
confidence: 99%
“…With the evolution of land plants (Graham, 1993), the salt tolerance of their ancestral marine algae, consisting of a salt requirement for amongst other membrane stability and enzyme functioning, has been lost. There are some salt tolerant mosses (Flowers et al, 2010), ferns show no salt tolerance, so most likely salt tolerance secondarily evolved in angiosperms (Fig. 2, Rozema, 1991Rozema, , 1996Flowers et al, 2008Flowers et al, , 2010.…”
Section: Evolution Of Salt Tolerance In Terrestrial Dicotyledonae Andmentioning
confidence: 99%
“…Attempts to improve the salinity tolerance of conventional crops have not been successful so far. This is because tolerance to salinity is a complex trait [4], involving multiple genes and having evolved multiple times independently among different lineages [7], leading to different mechanisms of salinity tolerance. A different promising strategy is to focus on the de novo domestication of halophytes.…”
Section: Introductionmentioning
confidence: 99%